Pengaruh Good Corporate Governance Terhadap Tax Avoidance Pada Perusahaan Yang Terdaftar di Jakarta Islamic Index (JII) - Mukhsin, Muhamad; Herawati, Mesi (Disclosure: Journal of Accounting and Finance, 2022)
The realization of the tax amnesty in 2016 made Indonesia ranked first in the practice of implementing tax amnesty in the world, but on the other hand there are still many companies that have not complied with tax payments. Good corporate governance should take an important role in minimizing tax avoidance practices. This study aims to examine the effect of Good Corporate Governance on tax avoidance. Good Corporate Governance is proxied by Institutional Ownership, Independent Board of Commissioners, Audit Committee and Company Size, while Tax Avoidace is proxied by Current Effective Tax Rate with the object of research being companies listed in the Jakarta Islamic Index (JII). This research is a quantitative research using regression analysis method. The regression results explain that; Institutional ownership has a significant positive effect on tax avoidance (0.0212 < 0.05), the Board of Independent Commissioners has no significant effect on tax avoidance (0.8451 > 0.05), the Audit Committee has a significant negative effect on tax avoidance (0.0498 < 0.05), Company Size has a significant positive effect on tax avoidance (0.0011 < 0.05).